2021
DOI: 10.1093/cdn/nzab011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Responses to Native Wheat Starch (MidsolTM 50) versus Resistant Wheat Starch Type 4 (Fibersym® RW): Standard versus Marketplace Testing Protocols

Abstract: Background To investigate the effect of RS on acute glycemic or insulinemic responses, the FDA indicates that control and RS-enriched foods must contain equivalent amounts of digestible carbohydrate. However, RS-containing foods typically contain less digestible carbohydrate per serving than control foods. Thus, controlling for digestible carbohydrate may yield different responses as compared with controlling for serving size. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The current study was conducted as a single-blinded randomized-controlled crossover trial, where all participants experienced all treatments. Methods and procedures were modified from Steele et al, [ 13 ]. Specifically, the timepoints of whole blood collection and the method of glucose analysis were modified.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study was conducted as a single-blinded randomized-controlled crossover trial, where all participants experienced all treatments. Methods and procedures were modified from Steele et al, [ 13 ]. Specifically, the timepoints of whole blood collection and the method of glucose analysis were modified.…”
Section: Methodsmentioning
confidence: 99%
“…Existing randomized controlled trials have shown beneficial effects of RS4 intake on glycemic and insulinemic responses [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. To test the benefits of RS4 for fiber food label classification, researchers often test at a 50 g amount of digestible carbohydrate [ 8 , 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorylated cross-linked RS4 produced from wheat starch is marketed as a dietary fiber that can be used as a stealth ingredient to swap higher-calorie starches without compromising palatability or major recipe alterations (29-31). We and others have shown that a diet supplemented with this food-ingredient may attenuate blood glucose and cholesterols, increase satiety, and lower body weight, fat, and inflammation (8,16,29,31,32). A similar RS4 product derived from maize has also demonstrated metabolic health benefits (33,34).…”
Section: Introductionmentioning
confidence: 97%